Romakép a mai magyar társadalomban - Székelyi, Mária; Örkény, Antal; Csepeli, György (Szociológiai Szemle, 2024)
The article presents findings of a study from a national sample on the attitudes members of the majority population reveal with regard to the mobility chances of the Roma population.Responses suggest three ways of upgrading: 1. a self-reliance strategy on the basis of internal resources, ignoring solidarity 2. a path of assimilation 3. an integration track implying both the maintenance of Roma identity and social help from outside.The study outlines complex cognitive structures leading to either the acceptence or refusal of any ways of adaptations explained above.